The Relation Between ‘Student Loyalty’ and ‘Student Satisfaction’ (A case of College/Intermediate Students at Forman Christian College) - Austin, Amoon Jawaid; Pervaiz, Sara (European Scientific Journal, ESJ, 2017)
Due to the increase in the number of educational institutions in the past few years, the competition has significantly increased. This change in the environment has shown the declining trends in enrollments and also in low quality students. It is becoming extremely important that policy makers of educational institutions find ways to increase the loyalty of their students. Such type of student loyalty can help in marketing the institutions by spreading a good word of mouth. In order to do so, institutions should find the areas which contribute more in student loyalty towards their institution. This would also help to identify ways of attracting prospective students with tailored and aggressive marketing programs. The study was conducted with College/Intermediate students of Forman Christian College (FCC), a twoyear data has been considered to find the relationship between â€œstudent satisfactionâ€ and â€œstudent loyaltyâ€ (spreading a good word of mouth and recommending their institution to others). 2,309, FCC students were surveyed, and correlation and regression analysis was performed to establish a model to predict â€œstudent loyaltyâ€ as a dependent, using â€œstudent satisfactionâ€ as an independent variable. After performing the data analysis it was discovered that some of the satisfaction areas contribute in student loyalty as compared to others. Based on the results some suggestions and recommendation were made by the author that can help in creating a positive word of mouth among their alumni students, which can help in attracting good students for FCC.